Application of oxidative process to degrade paraquat present in the commercial herbicide - Tadayozzi, Yasmin Saegusa [UNESP]; Santos, Felipe André dos [UNESP]; Vicente, Eduardo Festozo [UNESP]; Forti, Juliane Cristina [UNESP] (Taylor & Francis, 2021)
Paraquat is resistant to degradation by conventional treatments, being necessary to use treatments with greater effectiveness, such as advanced oxidative processes. In this work, different advanced oxidative processes were applied (Fenton, electro-Fenton, photoelectro-oxidation and photoelectro-Fenton) employing oxide electrodes to degrade Gramoxone, a commercial herbicide that contains paraquat in its composition. The degradation and formation of by-products were accompanied by high performance liquid chromatography, total organic carbon (TOC) and chemical oxygen demand (COD). The results showed that the photoelectro-Fenton process was the most efficient due to the synergistic effect, reaching 79% degradation of the initial compound and 82% and 71% removal of TOC and COD, respectively. After the application of the electro-Fenton and photoelectro-Fenton oxidation processes, short-chain carboxylic acids such as succinic acid, oxalic acid, acetic acid and formic acid were identified as by-products of the oxidation of Gramoxone. The results were satisfactory and deserve to be highlighted, as a commercial formulation was used, making the scenario more realistic.
Keywords: by-products; electro-Fenton; Fenton; Gramoxone; paraquat; photoelectro-oxidation